Evaluation of Symbiotic Nitrogen Fixation by Rhizobial Strains in Common Bean (Phaseolus Vulgaris L.) Using the 15N Isotope Dilution Method (Journal of Science and Technology, 2016)
The study was carried out under phytotron conditions to evaluate the symbiotic effectiveness of five strains of Rhizobium leguminosarum by. phaseoli (CIAT 144, CIAT 166, CIAT 652, CIAT 899 and Sweden 458) on two cultivars of common bean (Phaseolus vulgaris L.) using the "N isotope dilution method. Nitrogen as Ca (NO3)2 (5.736 atom% '5N excess) was applied at the rate of 20 mgN/kg soil. The two bean cultivars (Rondina and Stella) differed in their dry matter yield at well as N2 fixing abilities with the different rhizobial treatments. The per cent of plant N derived from the atmosphere (% Ndfa) averaged 47.6% for Rondina and 54.3% for Stella over all rhizobial strains. The actual amount of N2 fixed varied between 40 mg/pot and 89 mg/pot depending on the bean cultivar and rhizobial strain. Rondina averaged 53 mg fixed N/pot and Stella 74 mg fixed N/pot.There were differences in the predictions of symbiotic effectiveness of the rhizobial strains in the bean cultivars using both isotopic and non-isotopic parameters. Strains CIAT 144, CIAT 652 and CIAT 899 were, in decreasing order, the highest N2 fixers with Stella as were CIAT 652, CIAT 899 and CIAT 144 with Rondina. Using both parameters, strain CIAT 652 seemed to be the best fixer and strain Sweden 458 the worst in the two cultivars.